2017
DOI: 10.1049/iet-est.2016.0024
|View full text |Cite
|
Sign up to set email alerts
|

Fault mechanism study on Li‐ion battery at over‐discharge and its diagnosis approach

Abstract: A detailed research on fault mechanism of lithium (Li)-ion battery at over-discharge condition is reported in this study. Cells were cycled with different depths of discharge and reference performance tests were performed to extract parameters in dynamic and equilibrium conditions. The over-discharge process indicates that the abrupt change of temperature and impedance can be used for fault predication, while the parameter variations from federal urban driving schedule test can clearly identify the fault mode.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Common conditions include Li plating due to fast or lowtemperature charging or path-dependent aging; mild overcharge and overdischarge due to faulty or less-resilient sensors and management; nonuniform aging due to aggressive use or inadequate or faulty management; internal and external shorts due to latent manufacturing defects or incorrect use, inappropriate fixturing, or cell damage and aging; and divergent aging due to cell-to-cell variability. 17,[25][26][27][28][29][30][31][32][33][34][35][36][37][38] Literature surveys indicate the existence of a diverse set of diagnostics for LiB cells-diagnosing Li plating, [39][40][41][42][43][44] overcharge, [45][46][47] overdischarge, 45,48,49 internal shorts, [50][51][52][53] external shorts, [54][55][56] and electrode-and cell-level inhomogeneities 28,[57][58][59][60][61][62] -employing various thermal, electrochemical, acoustic, and entropy-based methods, often combined with different modeling-based approaches. Most of these methods are still in development; therefore, they have not been extended to module, string, or pack levels.…”
Section: Cell-level Diagnosticsmentioning
confidence: 99%
“…Common conditions include Li plating due to fast or lowtemperature charging or path-dependent aging; mild overcharge and overdischarge due to faulty or less-resilient sensors and management; nonuniform aging due to aggressive use or inadequate or faulty management; internal and external shorts due to latent manufacturing defects or incorrect use, inappropriate fixturing, or cell damage and aging; and divergent aging due to cell-to-cell variability. 17,[25][26][27][28][29][30][31][32][33][34][35][36][37][38] Literature surveys indicate the existence of a diverse set of diagnostics for LiB cells-diagnosing Li plating, [39][40][41][42][43][44] overcharge, [45][46][47] overdischarge, 45,48,49 internal shorts, [50][51][52][53] external shorts, [54][55][56] and electrode-and cell-level inhomogeneities 28,[57][58][59][60][61][62] -employing various thermal, electrochemical, acoustic, and entropy-based methods, often combined with different modeling-based approaches. Most of these methods are still in development; therefore, they have not been extended to module, string, or pack levels.…”
Section: Cell-level Diagnosticsmentioning
confidence: 99%
“…Although the cut-off voltage can be pre-set in the protection circuit, overcharge and overdischarge faults still occur in EVs due to the inconsistency among cells, inaccurate condition monitoring, and charging system faults [88]. For example, if the voltages of series cells are not monitored well in BMS, the cells that have the highest and lowest voltages will be overcharged and overdischarged, respectively, resulting in the rapid aging of the battery.…”
Section: Li-ion Battery Fault Mechanismsmentioning
confidence: 99%
“…After recharging, the newly regenerated SEI changes the electrochemical properties of the anode [95], resulting in an increase of resistance and the degradation of capac ity [96]. Repeated overdischarge will accelerate battery capacity degradation, the extent of which depends on the depth of discharge [88]. During overcharging, lithium deposition (mossy or dendritic type) will occur at the surface of the anode [97].…”
Section: Li-ion Battery Fault Mechanismsmentioning
confidence: 99%
“…Zhang and Wu et al [21,22] discovered that the positive electrode of a battery after discharging contained brass. Ye et al [23] observed that the temperature of the negative electrode was always higher than that of the positive electrode during overdischarging; an electrochemical reaction platform in which the Cu current collector was dissolved was observed at 0.5 V, and the overdischarge reduced the SEI film decomposition temperature.…”
Section: Of 14mentioning
confidence: 99%